2022
DOI: 10.1016/j.pmedr.2021.101687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organized activities on mental health in children and adolescents: An umbrella review

Abstract: Highlights This umbrella review included six systematic reviews of lower quality. A small positive impact of organized sport activities on youth mental health was found. Only two systematic reviews that studied organized non-sport activities could be included. Mixed results were found for impact of organized non-sport activities on youth mental health. Mediation or confounding through physical activity needs further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Most clearly, we find a consistent pattern of small beneficial effects on mental health linked to sports participation in accordance with previous evidence (Badura et al, 2021; Boelens et al, 2022). Both team and individual sports were found to have positive effects on three of the PedsQL domains—social functioning, emotional functioning, and the overall psychosocial score.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most clearly, we find a consistent pattern of small beneficial effects on mental health linked to sports participation in accordance with previous evidence (Badura et al, 2021; Boelens et al, 2022). Both team and individual sports were found to have positive effects on three of the PedsQL domains—social functioning, emotional functioning, and the overall psychosocial score.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our results suggest that most—but not all—of the relationship between extracurricular activity participation and adolescent outcomes is driven by confounding rather than causal effects of activity participation per se. Our findings comparing the random‐effects estimator with controls to the fixed‐effects estimator further indicate that adjustment for potential observed confounders (as is common in the literature—see e.g., Boelens et al, 2022; Bohnert et al, 2010; Farb & Matjasko, 2012; Shulruf, 2010) is unlikely to be sufficient to reliably estimate causal effects of extracurricular activity participation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…An umbrella review of systematic reviews and meta-analyses found a small positive impact of participation in organized sports on mental health in children and adolescents. 60 This was not related to any specific type of organized sport activity. The findings of a recent study from Canada using a large and diverse sample of high school students suggest that sport participation should be promoted for the prevention and management of adolescent mental illness.…”
mentioning
confidence: 88%
“…Previous reviews have reported physical and psychosocial outcomes as being associated with organized PA (e.g. [ 12 , 13 ]), non-organized PA (e.g. [ 14 , 15 ]) and active transport (e.g.…”
Section: Introductionmentioning
confidence: 99%